Determination of the draft force for different subsoiler points using discrete element method - Bo, Li; Rui, Xia; Fanyi, Liu; Jun, Chen; Wenting, Han; Bing, Han (International Journal of Agricultural and Biological Engineering, 2016)
Generally, a subsoiler is comprised of a shank and a point. The point shape has a significant effect on the draft force of a subsoiler. In this study, the draft force of subsoilers with four different points were compared under the speed of 0.8 m/s and the depth of 350 mm in the soil bin. Discrete Element Method (DEM) was applied in simulating the working process of the subsoiler. The stiffness of soil particles used in DEM was calibrated by comparing the simulated draft force of a standard arc-shaped subsoiler with the experiment. The calibrated soil particle stiffness was 1.1×104 N/m. The validated model was then used to compare the draft force of subsoilers with four different points under the same condition in the test. Results showed that different points would cause different draft forces. The subsoiler with short chisel point caused the smallest draft force (2885 N) while the point with short face and wings had the largest force (4474 N). The relative errors of the simulated results were less than 4%, which proved that DEM was an effective way for predicting the draft force of subsilers. The velocity field and contact force filed could show the movement of soil around the subsoiler.Keywords: subsoiler, point shape, draft force, chisel point, DEM, conservation tillageDOI: 10.3965/j.ijabe.20160903.2210Citation: Li B, Xia R, Liu F Y, Chen J, Han W T, Han B. Determination of the draft force for different subsoiler points using discrete element method. Int J Agric & Biol Eng, 2016; 9(3): 81－87.